Hazardous metals coupled with increasing summer diurnal temperature range contributed to growth decline of two oak species in a heavily industrialized area - Constantin Nechita; Andreea Maria Iordache; Tomas Pluhacek; Filip Gregar; J. Julio Camarero (Journal of Hazardous Materials, 2025)

Tracing the transfers of raw materials in the Gravettian of Moravia and Silesia - Martin Moník; Zdeňka Nerudová; Martin Novák; Antonín Přichystal; Filip Gregar; Petr Hamrozi; Tomáš Pluháček (Quaternary International, 2025)

Chemical fingerprinting of European radiolarites and raw material economies from the Moravian Aurignacian - Martin Moník; Zdeňka Nerudová; Filip Gregar; Tomáš Pluháček; Jitka Součková; Petr Hamrozi (Archaeological and Anthropological Sciences, 2025)
Chemical fingerprinting and spectrophotometry were combined to conduct a provenance analysis of radiolarite artefacts from three Moravian (Czech Republic) Aurignacian sites of Tvarožná I, Nová Dědina I and Milovice I. Of the different methods used, laser ablation with inductively coupled plasma mass spectrometry (LA-ICP-MS) was the best suited to distinguish the different areas containing radiolarite outcrops. Based on their chemical fingerprint, Moravian Aurignacian radiolarite artefacts were most likely imported from the western Slovak part of the Pieniny Klippen Belt. The abundant radiolarite outcrops in the Vienna region were apparently ignored, with the possible exception of two radiolarite artefacts from the Milovice I site. However, these could also have been manufactured from gravel radiolarites found around the site. Upon assigning other lithologies from Aurignacian sites in Moravia to their areas of provenience, it transpired those imports derived primarily from non-south-western regions. A similar situation was previously observed in the Moravian Szeletian, possibly indicating information exchange between the two Upper Palaeolithic cultures. Although the subsequent Gravettian culture relied more on long-distance imports, north-eastern − south-western movements and transfers were predominant up until the end of the Moravian Upper Palaeolithic, largely due to the communication corridor of the Moravian Gate. Upper Palaeolithic Moravia was an important source of raw materials and a hub for gathering other materials and information from concrete supply zones, while others were neglected.

Investigating the impact of paleoclimatic conditions and diagenesis on the genesis of Permian Continental Red Beds: A case study from the Bohemian Massif, Czechia - Salahadin Shahrokhi; Ondřej Bábek; Howri Mansurbeg; Lukáš Ackerman; Daniel Šimíček; Filip Gregar; Michal Kořenek (Sedimentary Geology, 2024)

Direct elemental analysis of plant oils by inductively coupled plasma mass spectrometry: Simple sample dilution combined with oxygen introduction into the plasma - Filip Gregar; Jakub Grepl; David Milde; Tomáš Pluháček (Food Chemistry, 2024)